Development of an integrated fuzzy-logic-based missile guidance law against high speed target. - Chun-Liang Lin (IEEE Transactions on fuzzy systems)
How to develop a novel missile guidance law that can act effectively against very high speed incoming targets, such as ballistic missiles, has been a major concern in the defense technique. It has been unveiled recently in the literature that the most effective way for a lower speed interceptor to successfully engage an incoming target with very high speed is to limit the aspect angle between the missile and target flight path to within 180° plus or minus few degrees. On the basis of this requirement, a new integrated fuzzy guidance law is developed in this paper against very high-speed maneuverable targets on three-dimensional space. An integrated fuzzy type guidance law is explored for midcourse and terminal phases. It is shown that the integrated guidance scheme offers excellent tracking performance as well as performance sensitivity with respect to some parametric variations.